STUDY OF THE MODERN PARADIGM OF EDUCATIONAL DIPLOMACY: THE CASE OF UKRAINE - Mietule, Iveta; Hushko, Serhii; Maksymova, Irina; Purii, Hanna; Kulishov, Volodymyr (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The article examines the modern paradigm of education diplomacy through the elements of public diplomacy instead of classical understanding of diplomacy, namely, the formation of the image of an educational institution, interpersonal relations of participants in the educational process and the definition of new content in the global educational space. Besides, a discourse analysis is conducted, the main tasks of education diplomacy are formulated and defined. The methodological foundations of education diplomacy functioning are considered basing on generalizations of the experience and observations covering this issue, which indicate the multi-vector nature and relevance of the proposed research. Ukraine takes an important place in the development of global education diplomacy, due to positioning itself as a country of cultural and educational values on the international arena. The expert opinions of scientists studying the issue of education diplomacy from the point of view of current development, advantages and challenges are given in the article.  An integral part of education is scientific diplomacy, which has been gaining special relevance, since the publication and content of educational and scientific literature determine not only education in general, but also the educational and informational context of the country, in particular. Emphasizing positive trends and achievements in the field of education diplomacy, the authors, on the other hand, listed some problems and challenges in Ukraine, proposed relevant conclusions regarding the in-depth study of the issue. The result of the research was the proposed cluster model of educational diplomacy.